Intellectual Disability and Parenthood - Isack Kandel; Mohammed Morad; Gideon Vardi; Joav Merrick (The Scientific World Journal)
Parenthood in persons with intellectual disability (ID) is an issue of concern for the family, guardians, and professionals as there are many sentiments and problems involved: financial, technical, medical, legal, and above all moral. People with intellectual, developmental, or other disabilities have feelings, want relationships, and are able to have children also. The attitude of society has changed through time from the early eugenic concern with heredity and fertility, to a focus on the risk to the children due to parental neglect or abuse, to acceptance and a search for solutions to parental training and support. This change can be seen as a result of a shift from institutional care to community care and normalization. This paper reviews available research, prevalence, service issues, experience from around the world, and relates to the situation in Israel. Jewish Law has been very progressive regarding the possibility of marriage between persons with ID (in contrast to American Law where historically this right has been denied, until recently). Recent research has shown that, in the case of such a union resulting in children, although they require some supervision, family, friends, and social welfare agencies have scrutinized these families so much they are in constant fear of their child being taken away. There is little information on the number of such cases and an overall dearth of information on the effects on the children, although one recent study from the U.K. has shown a varied picture of resilience and a close, warm relationship later on with the family and especially the mother.